Adherence to Exercise in People with Lung or Head and Neck Cancer: Self-Reported Symptoms and Motivation During Cancer Treatment Need to Be Considered - Pedroso, Matheus [UNESP]; Grigoletto, Isis [UNESP]; Oliveira, Letícia [UNESP]; Martins, Sarah [UNESP]; Costa, Lara [UNESP]; Pozo, Karina [UNESP]; Borges, Paloma [UNESP]; Regio, Livia [UNESP]; Duarte, Isabela [UNESP]; Cavalheri, Vinicius; Ramos, Ercy [UNESP] (MDPI, 2024)
Objectives: Symptoms and motivation may impact adherence to home-based exercise training programs (HETP) during cancer treatment (CT) for lung or head and neck cancer. This study aimed to identify self-reported symptoms and their frequency, as well as motivation towards an HETP during CT for primary lung or head and neck cancer. Associations between symptoms and motivation with HETP adherence were also investigated. Methods: Participants underwent CT combined with an HETP that included aerobic (walk-based) and resistance training (Theraband®). Weekly assessment was conducted using a questionnaire developed by the researchers, evaluating the presence of symptoms. A scale (0 to 10) was used to assess motivation towards the HETP. Adherence was defined as the ratio between HETP sessions completed vs. the number prescribed. Symptom frequency was recorded as the number of weeks a symptom was experienced. Linear regression was used to explore associations. Results: Twenty-four participants were included (61 ± 7 yr; 21 males; head and neck cancer n = 18; median treatment duration: 9 [7 to 11] weeks). The most commonly reported symptoms were fatigue (33%), malaise (24%) and dysphagia (23%). Average score for motivation to exercise was 6.4 ± 2.0. Adherence to the HETP was 47%. Malaise was associated with reduced adherence to HETP (p = 0.002), explaining 35% of the variance. Motivation was associated with increased adherence (p = 0.008), explaining 28% of the variance. Conclusions: Fatigue, malaise and dysphagia were among the most frequently reported symptoms during treatment. Malaise and self-motivation to exercise can significantly influence adherence to HETPs. Symptom and motivational support might be necessary when implementing HETPs during CT.
Keywords: exercise; head and neck neoplasms; lung neoplasms; motivation; neoplasms; symptom assessment; symptom burden